EXPERIMENTAL FISHING OFF ULLAL (MANGALORE) - Prabhu, M S; Ramamurthy, S; Kuthalingam, M D K; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
Though an average of 1685 tonnes* of fish is landed annually by the mechanised boats of Mangalore, which operate during late October to early May within the 25 meter region, no information is available on the abundance, catch composition and distribution of the fishery of this area. Hence, experimental fishing was undertaken at 12 and 25 meters off UUal and the results are piesented here which may be of use for commercial exploitation of the fishery of this region- The earlier accounts on the exploratory fishing, however, relate to certain other parts of the west coast of India (Srivatsa, 1953a, b Gopinath, 1954; Jayaraman et al., 1959) except for a brief report on shrimp trawling conducted for four weeks in March/April of 1955 and 1956 between depths of 2 and 10 meters off Mangalore (Shariff, 1959).